Tumor prevention and genetics III - Senn, Hans-Jörg. (Recent results in cancer research, 2005)
Lifestyle and medical approaches to cancer prevention -- Application of genetics to the prevention of colorectal cancer -- genetics and prevention of oesophageal adenocarcinoma -- Preclinical models relevant to diet, exercise, and cancer risk -- Individualizing interventions for cancer prevention -- Can animal models help us select specific compounds for cancer prevention trials? -- Problems with using biomarkers as surrogate end points for cancer: a cautionary tale -- Can a marker be a surrogate for development of cancer, and would we know it if it exists? -- How should we move the field of chemopreventive agent development forward in a productive manner? -- The problems with risk selection; scientific and psychosocial aspects -- Chemoprevention of lung cancer -- Anti-nicotine vaccination: where are we? -- Primary prevention of colorectal cancer: lifestyle, nutrition, exercise -- Chemoprevention of colorectal cancer: ready for routine use? -- Screening of colorectal cancer: progress and problems -- The role of endogenous hormones in the etiology and prevention of breast cancer: the epidemiological evidence -- Innovative agents in cancer prevention -- The IARC commitment to cancer prevention: the example of papillomavirus and cervical cancer -- Health economics in the genomic age -- Screening for cancer: are resources being used wisely?.